In vitro DNA Inversions Mediated by the PsrA Site-Specific Tyrosine Recombinase of Streptococcus pneumoniae - Li, Jingwen; Wang, Juanjuan; Ruiz-Cruz, Sofía; Espinosa, Manuel; Zhang, Jing-Ren; Bravo, Alicia (Frontiers in Molecular Biosciences, 2020)
Site-specific recombination is a DNA breaking and reconstructing process that plays important roles in various cellular pathways for both prokaryotes and eukaryotes. This process requires a site-specific recombinase and direct or inverted repeats. Some tyrosine site-specific recombinases catalyze DNA inversions and regulate subpopulation diversity and phase variation in many bacterial species. In Streptococcus pneumoniae, the PsrA tyrosine recombinase was shown to control DNA inversions in the three DNA methyltransferase hsdS genes of the type I restriction-modification cod locus. Such DNA inversions are mediated by three inverted repeats (IR1, IR2 and IR3). In this work, we purified an untagged form of the PsrA protein and studied its DNA-binding and catalytic features. Gel retardation assays showed that PsrA binds to linear and supercoiled DNAs, containing or not inverted repeats. Nevertheless, DNase I footprinting assays showed that, on linear DNAs, PsrA has a preference for sites that include an IR1 sequence (IR1.1 or IR1.2) and its boundary sequences. Furthermore, on supercoiled DNAs, PsrA was able to generate DNA inversions between specific inverted repeats (IR1, IR2 and IR3), which supports its ability to locate specific target sites. Unlike other site-specific recombinases, PsrA showed reliance on magnesium ions for efficient catalysis of IR1-mediated DNA inversions. We discuss that PsrA might find its specific binding sites on the bacterial genome by a mechanism that involves transitory non-specific interactions between protein and DNA.